Public or private equity? How accelerated IPOs can increase competition in offerings - Jenkinson, T (University of Oxford, 2008)
This clinical paper analyses a new way of conducting IPOs which has recently been introduced in the U.K. The essential feature of Accelerated IPOs (aIPOs) is that investors from syndicates to bid for the entire offering, and then execute an immediate IPO (within a week). Vendors can use an auction to determine whether the valuation is higher in private equity, trade, or public equity hands. aIPOs address two problems that regulators and academics have associated with conventional IPOs conducted via bookbuilding: inaccurate valuation and questionable use of discretion over allocation. Conflicts of interest are avoided as the advisors who organise aIPOs work for the investors rather than the issuing company.